An efficient emergency, healthcare, and medical information system - Hameed, Shihab A.; Hassan Abdalla Hashim, Aisha; M. Sharifudeen, Shahina Shabnam; Meho, Vladimir; Khalifa, Othman Omran (Computer Science Journals, 2008)
Many of the current Malaysian medical information and emergency systems are still paper-based and stand alone systems that do not fully utilize the Internet, multimedia, wireless and real time technologies. This research work focuses on developing an integrated Emergency, Healthcare, and Medical Information System (IEHMS) that can overcome many of the problems in the current systems. The main aim of this work is to incorporate the real-time and mobility technologies with medical emergency systems. Our proposed system can offer: SMS, MMS, live audio and video coverage. A prototype for the proposed system is implemented using open source tools.